Clinical Manifestations and Viral Triggers of Childhood Multiple Sclerosis: Multinational Study - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The clinical manifestations, outcome, and viral triggers in 137 children (<18 years old) with multiple sclerosis (MS) and 96 controls, enrolled between 2003 and 2006 from diverse multinational geographic regions, were studied by researchers from the Divisions of Neurology and Microbiology, The Hospital for Sick Children, Toronto; Stony Brook University Medical Center, USA; and other centers in Canada, USA, Argentina, Russia, Italy, and Sweden.